Economic issues in Irish forestry - O'Connor, R.; Kearney, B. (Statistical and Social Inquiry Society of Ireland, 1993)
The main objective of this paper is to show the extent to which forestry can provide income and employment in the State. To put the subject in context the paper commences by showing the areas under forest in Ireland and other EC countries. There follows a brief history of forestry in Ireland from the beginning of the 17th century to the present time. We next examine recent developments in forestry including the introduction of the current forestry operational programme and the problems of achieving the planting targets. The next section deals with the impact of forestry on rural areas with particular emphasis on land use and rural employment. This is followed by a section dealing with the economics of private planting. The paper concludes with a discussion on supply and demand trends for timber, and Irish trade in wood and wood products.
Read before the Society, 22 April 1993
Keywords: Forestry; Timber trade; 314.15